IQTIBAS : Mendeteksi Prosa dan Syair dalam Al-Qur’an dan Hadis - Abdurrahman Abdurrahman; Mirsa Triandani; Harun Al Rasyid (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
A few centuries after the demise of the Qur'an, the scholars formulated language, usub and literature in order to study and deepen the content of the Qur'an, which gave rise to many scientific disciplines, among others in the field of language studies, nahwu and sorof , related to the style of language and literature was born balaghoh discipline with branches of study, ma'ani, bayan and badi '. In Badi Science, iqtibas is defined as follows